Design of Hybrid Fractal Integrated Half Mode SIW Band Pass Filter with CSRR and Minkowski Defected Ground Structure for Sub-6 GHz 5G Applications - Muchhal, Nitin; Elkhouly, Mostafa; Vintimilla, Renato Zea; Chakraborty, Arnab; Srivastava, Shweta (Photonics, 2022)
A compact and wide-stop band half mode substrate integrated waveguide (HMSIW) filter, incorporated with a hybrid fractal on the upper plane and a complementary split ring resonator (CSRR), along with a defected ground structure (DGS) etched on the bottom plane, is proposed for 5G sub-6 GHz application. A CSRR reduces the resonant frequency causing size miniaturisation by approximately 40% by augmenting the equivalent inductance and capacitance of the CSRR. Further, the low-pass characteristics of the DGS aid in suppressing out-of-band spurious harmonics. A two-pole band pass filter (BPF) is fabricated using FR4 (flame retardant) to validate the design. The results confirm that the proposed filter has a pass band from 3.75 GHz–5.12 GHz with spurious response below −20 dB > 4f0.